Three-Dimensional Monitoring of Zelongnong Glacier, China, with the PO-MSBAS Technique - Xinyi Zhai; Chaoying Zhao; Bin Li; Wenpei Wang; Xiaojie Liu (Remote Sensing)
High-precision monitoring of glacier motion provides crucial information for a thorough understanding of the dynamic characteristics and development patterns of glaciers, which serves as a scientific basis for the prevention and management of glacier-related disasters. Zelongnong Glacier, located in Tibet, China, has experienced glacier surges, collapse, and hazard chains four times in the last 70 years. On 10 September 2020, a major glacier hazard chain occurred in this region. To reveal the influencing factors of the glacier motion, we monitor the Zelongnong Glacier motions with 65 scenes of TerraSAR/PAZ images from 2022 to 2023, where the Pixel Offset Multidimensional Small Baseline Subset (PO-MSBAS) method is employed for three-dimensional time series inversion. As the registration window size directly affects the matching success rate, deformation accuracy, and signal-to-noise ratio (SNR) during the offset tracking processing, we adopt a variable window-weighted cross-correlation strategy. The strategy balances the advantages of different window sizes, effectively reducing noise while preserving certain details in the offset results. The standard deviation in stable areas is also significantly lower than that obtained using smaller window sizes in conventional methods. The results reveal that the velocity of the southern glacier tributary was larger than the one in the northern tributary. Specifically, the maximum velocity in the northern tributary reached 45.07 m/year in the horizontal direction and −7.45 m/year in the vertical direction, whereas in the southern tributary, the maximum velocity was 50.15 m/year horizontally and 50.66 m/year vertically. The southern tributary underwent two bends before merging with the mainstream, leading to a more complex motion pattern. Lastly, correlation reveals that the Zelongnong Glacier was affected by the combined influence of temperature and precipitation with a common period of around 90 days.